(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Rhinosinusitis occurs much more often than it is diagnosed, since in some cases the clinical picture of acute sinusitis is masked ¬by the symptoms of acute viral infections. However, it is believed that sinusitis with influenza and ARVI should be considered not only as their complications, but also as their manifestation. In the development of the inflammatory process in the nasal cavity and paranasal sinuses, in addition to external causes (climatogeographic conditions, level of infectious diseases, environmental conditions, nutritional patterns, ¬stressful situations) that cause disturbances in mucociliary transport, anomalies in the structure of the intranasal structures and the ethmoidal labyrinth can play an important role.